Analisis pengaruh pendapatan asli daerah, dana alokasi umum, penanaman modal dalam negeri dan penanaman modal asing terhadap produk domestik regional bruto di provinsi Jawa Timur - Nurlaili Tito Wardani; Muchtolifah Muchtolifah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
The scientific study aims to determine the ipact or effect of Region own source Revenue, General Allocation Fund, Domestic Invesment, and Foreign Invesment in Gross Domestic Regional Product, as well as knowing the government’s efforts in overcoming the decline in Gross Domestic Regional Product. This is a quantitative scientific study. Quantitative data used is secondary data originating from the BPS Jatim website between 2011 and 2020. The scientific study uses multiple linier analysis with F analysis tets and t analysis test. From the results of the analysis it isknown that Region own source Revenue, General Allocation Fund, Domestic Invesment, dan Foreign Invesment have a significant effect on Gross Domestic Regional Product. Region own sourec Revenue sigificant impact on Gross Domestic Regional Product, whereas General Allocation Fund, Domestic Invesmemnt, adn Foreign Invesment no significant impact. Efforts made by the government in overcoming the decline in Gross Domestic Regional Product there are 2 ways, namely deferring income tax and providing additional funds to reduce the economic impact.